Drones for Dummies - LaFay, Mark (Hoboken, New Jersey: John Wiley & Sons, Inc, 2015)
"Drones For Dummies provides you with the information you need to find and purchase the right drone for your needs, examples of ways to use a drone, and even drone etiquette and the laws and regulations governing consumer drone usage. Plus, you'll discover the basics of flight, including how to use a drone to capture photos and video" --
Getting started with drones -- Before you fly -- Miracle of flight -- Aerial photos and videos -- Part of tens.
Includes index.
Keywords: Drone aircraft; Vehicles, Remotely piloted; Drone aircraft; Drone aircraft; Vehicles, Remotely piloted; Drone aircraft